Real-world evidence on disparities on the initiation of Ticagrelor versus Prasugrel in patients with acute coronary syndrome - Yildirim, Mustafa; Müller-Hennessen, Matthias; Milles, Barbara Ruth; Biener, Moritz; Hund, Hauke; Frey, Norbert; Giannitsis, Evangelos; Salbach, Christian (Journal of the American Heart Association, 2023)
Background: Management of patients with non-ST-segment-elevation acute coronary syndrome (NSTE-ACS) is based on 2020 European Society of Cardiology guidelines, which recommend the preferential use of prasugrel over ticagrelor. Because the selection of the respective P2Y12 inhibitor has to consider label restrictions, we sought to evaluate the proportion of patients qualifying for either ticagrelor or prasugrel and reasons for noneligibility in an unselected cohort of patients with acute coronary syndrome. Methods and Results In this retrospective observational study, patients with ST-segment-elevation myocardial infarction (STEMI) or NSTE-ACS presenting consecutively during a 24-month period were enrolled. The eligibility of patients for a dual antiplatelet therapy option was assessed retrospectively. A total of 1502 patients had confirmed acute coronary syndrome (287 STEMI and 1215 NSTE-ACS). Eligibility for ticagrelor and full-dose prasugrel differed significantly for STEMI and NSTE-ACS (93% versus 51%, P<0.0001 versus 80% versus 31%, P<0.0001). Eligibility remained significantly lower (STEMI 78% versus NSTE-ACS 52%) if low-dose prasugrel was considered. Patients eligible for full-dose prasugrel had lower ischemic risk per GRACE (Global Registry of Acute Coronary Events) score (109 points [90-129 points] versus 121 points [98-146 points], P<0.0001) and lower bleeding risk (14 points [13-15 points] versus 20 points [12-29 points], P<0.0001) per PRECISE-DAPT (Predicting Bleeding Complications in Patients Undergoing Stent Implantation and Subsequent Dual Antiplatelet Therapy) score. Conclusions In real life, eligibility for prasugrel in patients requiring dual antiplatelet therapy is considerably lower than for ticagrelor, even in a cohort with high rates of coronary angiography and percutaneous coronary interventions. The recommended use of prasugrel over ticagrelor in current acute coronary syndrome guidelines contrasts with our observations of a substantial disparity on the eligibility. This important aspect has not received appropriate attention yet. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT05774431.
Gesehen am 04.10.2023